Mechanical behavior of 3d printed poly(ethylene glycol) diacrylate hydrogels in hydrated conditions investigated using atomic force microscopy - Hakim Khalili, Mohammad; Panchal, Vishal; Dulebo, Alexander; Hawi, Sara; Zhang, Rujing; Wilson, Sandra; Dossi, Eleftheria; Goel, Saurav; Impey, Susan A.; Aria, Adrianus Indrat (American Chemical Society, 2023)
Three-dimensional (3D) printed hydrogels fabricated using light processing techniques are poised to replace conventional processing methods used in tissue engineering and organ-on-chip devices. An intrinsic potential problem remains related to structural heterogeneity translated in the degree of cross-linking of the printed layers. Poly(ethylene glycol) diacrylate (PEGDA) hydrogels were used to fabricate both 3D printed multilayer and control monolithic samples, which were then analyzed using atomic force microscopy (AFM) to assess their nanomechanical properties. The fabrication of the hydrogel samples involved layer-by-layer (LbL) projection lithography and bulk cross-linking processes. We evaluated the nanomechanical properties of both hydrogel types in a hydrated environment using the elastic modulus (E) as a measure to gain insight into their mechanical properties. We observed that E increases by 4-fold from 2.8 to 11.9 kPa transitioning from bottom to the top of a single printed layer in a multilayer sample. Such variations could not be seen in control monolithic sample. The variation within the printed layers is ascribed to heterogeneities caused by the photo-cross-linking process. This behavior was rationalized by spatial variation of the polymer cross-link density related to variations of light absorption within the layers attributed to spatial decay of light intensity during the photo-cross-linking process. More importantly, we observed a significant 44% increase in E, from 9.1 to 13.1 kPa, as the indentation advanced from the bottom to the top of the multilayer sample. This finding implies that mechanical heterogeneity is present throughout the entire structure, rather than being limited to each layer individually. These findings are critical for design, fabrication, and application engineers intending to use 3D printed multilayer PEGDA hydrogels for in vitro tissue engineering and organ-on-chip devices.
Keywords: poly(ethylene glycol) diacrylate; 3D printing; AFM; heterogeneous modulus; cross-linking density; hydrogels